The Influence of Profitability, Liquidity, Leverage, Activity and Company Size on Sustainability Report Disclosure - Haris, Haris; Negoro, Dimas Angga (Universitas Pamulang, 2021)
Sustainability Report is the practice of disclosure, accountability and measurement of organizational (company) performance in achieving sustainable development goals to both internal and external stakeholders. On this basis, the study aims to determine the form of business responsibility that is oriented towards fulfilling public expectations of the existence of a business in the hope that the company will gain public legitimacy. This study aims to determine the effect of profitability, liquidity, leverage, activity, company size on sustainability report disclosure, using panel data regression on 12 companies engaged in the mining industry listed on the Indonesia Stock Exchange and actively distributing sustainability reports and annual reports during the period from 2014 to 2018. This study uses panel data regression, the dependent variable in this study is the sustainability report as measured by the sustainability discloser index under the parameters of the Global Reporting Initiative (GRI). The results of the study indicate that the firm size variable affects the disclosure of the sustainability report, and Liquidity Profitability, Leverage, whilst the activity has no effect on the sustainability report.